Comportamento dinâmico em torres de aerogeradores - Souza, Andressa Jales de (2018)
This work studies the wind’s dynamic behavior (random load) on wind turbines. The analyzed structure was simplified as a concentrated mass at the upper end of the tower in order to simulate a wind turbine. This thesis presents wind turbines state of art, describing its models and major components. Measurements were made placing sensors (piezoelectric accelerometers) at four points around the turbine’s tower, which one of them was placed in the wind’s direction and the others positioned 90º to each other. Environmental aspects of the ground /structure, that could help or hinder the studied structure proper functioning, were discussed. Thereafter, analytical and experimental concepts are presented in order to assist the understanding of structure’s natural behavior analysis, while explaining the wind turbines’ most relevant dynamics aspects. The field results of the vibration modes of the tower structure were measured and analyzed. In conclusion it is inferred that there is a small discrepancy between the experimental values of the modes of vibrations and those of the simplified analytical model.